2020
DOI: 10.20472/es.2020.9.2.008
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of the Introduction of Circular Business Models Within Rural Smes of Eu

Abstract: Recently the circular economy has got a lot of attention within discussions of policy makers, academics and practitioners. The circular economy proposes the treatment of environmental and climate change problems, simultaneously promising benefits for the business. The circular economy promotes the reduction of the consumption and reuse or recycling of the resources that in various aspects contradicts traditional business models that stream to linear growth of sales of their products. Yet the circular economy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…In rural SMEs, both in the manufacturing and agriculture sectors, Uvarova et al (2020) observed challenges in the environment for innovation, innovation policies and support measures, lack of workforce and low competitiveness in the industry within rural SMEs. These SMEs have rarely heard about the CE and even less about CBMs.…”
Section: Resultsmentioning
confidence: 99%
“…In rural SMEs, both in the manufacturing and agriculture sectors, Uvarova et al (2020) observed challenges in the environment for innovation, innovation policies and support measures, lack of workforce and low competitiveness in the industry within rural SMEs. These SMEs have rarely heard about the CE and even less about CBMs.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Ruggieri et al (2016) find that fragmented regulation hampers the circular transition. The overarching barrier for rural SMEs in the EU is the lack of an appropriate environment to introduce circular business models (CBMs) (Uvarova et al, 2020). Roosendaal (2018) argues that entities face the issue of cultural barriers, namely the lacking consumer interest in circular products.…”
Section: Macro-level Barriersmentioning
confidence: 99%
“…Reflecting on the absence of domestic support, Uvarova et al (2020) assert that strategic EU objectives and EU structural funds could catalyze rural SMEs from six countries to redesign their business models towards circularity. Similarly, Binek and Al-Muhannadi (2020) propose that SMEs should try to access EU funds and support, in case the domestic government does not offer beneficial solutions.…”
Section: Macro-level Enablersmentioning
confidence: 99%
See 2 more Smart Citations